2020 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE) 2020
DOI: 10.1109/tale48869.2020.9368330
|View full text |Cite
|
Sign up to set email alerts
|

Transit Traditional Face-to-Face Teaching to Online Teaching during the Outbreak of COVID-2019

Abstract: COVID-2019 outbroke in China at the beginning of 2020. Traditional face-to-face teaching cannot be achieved during the epidemic, and all schools across the country turned to online teaching. However, online education still faces many difficulties, and the most important question is how to ensure teaching quality. In this paper, we discussed some pedagogical approaches, including online teaching with the enhanced design of interactions, learning theories and problem-based learning, which are useful for designin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Low network coverage has become a key obstacle to rural online education, as evidenced in many previous studies. In Wan et al's study of the impact of COVID-19 on rural China [5], they found that an average of 70% of the students indicated that the internet signal was unstable.…”
Section: Poor Infrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…Low network coverage has become a key obstacle to rural online education, as evidenced in many previous studies. In Wan et al's study of the impact of COVID-19 on rural China [5], they found that an average of 70% of the students indicated that the internet signal was unstable.…”
Section: Poor Infrastructurementioning
confidence: 99%
“…Teacher assistance can reduce such difficulties for students. In urban areas of China, before online teaching starts, teachers will teach students how to participate in online courses through instant messages and pre-recorded videos [5]. After the lesson, teachers also provide recordings for students to review.…”
Section: Lacking In Learning Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, asynchronous teaching via Moodle illustrates some insufficient of teaching when one is looking for real-time exchange. For the authors [15], face-to-face interaction between teaching actors is a key factor in improving the quality of online teaching. This synchronous teaching modality reflects traditional classroom teaching where students become actively involved in their learning by interacting with each other, but also with their teacher to produce their educational activities.…”
Section: B Technological Background In E-learningmentioning
confidence: 99%